PENGARUH MEDIA BOOKLET TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TERKAIT KEBERSIHAN DALAM MENSTRUASI DI PONDOK PESANTREN AL-ISHLAH DEMAK TRIWULAN II TAHUN 2017 - Wanodya Puspitaningrum; Farid Agusyahbana; Atik Mawarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2017)
The poor personal hygiene of menstruation has a major effect on morbidity and complications. One of the factors that led to the lack of personal hygiene behavior during menstruation is because of the lack of knowledge and understanding of menstrual hygiene. More than 50% of young women in India have poor knowledge of menstrual hygiene. Based on previous research, 59.1% of adolescent girls in Pondok Pesantren Ulul Albab Sukoharjo have an unfavorable attitude in personal hygiene during menstruation. The purpose of this study is to determine the effect of booklet media on the knowledge and attitude of young women related to menstrual hygiene at Pondok Pesantren Al-Ishlah Demak. This is a pre-experimental study using a one-pretest-posttest design. The sample in this research used a population of 55 girls. Data analysis of univariate and bivariate using Sign Test with α=5%. The average score of knowledge of menstrual hygiene prior to the giving of booklet media was 8.29 whereas the mean score of knowledge of menstrual hygiene after giving the booklet was 10.64. The result of the research showed that the influence of media booklet on the change of knowledge (p=0.0001). The average score of menstrual hygiene before presentation of the booklet was 35.75 while the mean postmenopausal hygiene score after giving the booklet was 38.91. The result of this research indicate the effect of media booklet on attitude change (p=0.0001). Suggestions that can be given are increasing knowledge and attitude about hygiene during menstruation by forming small groups with routine mentoring. The conclusion of this research is giving of booklet media influencing knowledge and attitude of adolescent girl related to menstrual hygiene.